PENINGKATAN KETERAMPILAN MENULIS TEKS PERSUASI MENGGUNAKAN STRATEGI MENULIS TERBIMBING DAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL - Mui?in, Mui?in; Priyadi, A. Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted on Grade VIII Students of Semester 2 of SMP Negeri 7 Tayan Hilir of Sanggau Regency. The research carried out on learning materials to write text persuasion. In particular, this study uses guided writing strategies and contextual learning approaches. The guided writing strategy and the contextual learning approach are intended to improve the ability to write persuasion texts.This research uses descriptive research method with qualitative research form. The first stage is, pre action, second stage is cycle I, third stage that is, cycle II, and fourth stage that is, cycle III Based on the research conducted, got the conclusion that there is an increase to the result of writing the text of persuasion. The persuasion text produced by the students has improved in several aspects, namely the spelling aspect consisting of the use of punctuation, letter writing, and word writing, then the dictionary aspect consisting of, the special diction and the general diction in the persuasion text. Here is the average increase in each cycle. Originally the average value on the pre-action of 67.5 to 70 in the first cycle increased by 2.5%. Then, on the second cycle there was an increase in the average value of 70 to 77 in the second cycle has increased by 7%. In the third cycle there was an average increase of 77 to 82 in the third cycle of 5%. Keywords: Persuasion Text. Guided Approach and Contextual Learning Strategy.